Please Help!!!

Let z=root3-i and w=-2-2i.

Part I: Convert z and w to polar form.

Part II: Calculate wz using De Moivre's theorem. Express your answer in polar(r(cos theta+i sin theta)) form.

Part III: Calculate z^2. Express your answer in rectangular (a+bi) form.

Part IV: Calculate w^4. Express you answer in polar (r(cos theta+i sin theta)) form.

Respuesta :

Part I: The complex number √3-i in the polar form will be [tex]2(cos210^0+isin210^0)[/tex]

The complex number -2-2i in the polar form will be  [tex]2\sqrt{2}(cos45^0+isin45^0)[/tex]

Part II: The expression of the product of wz in polar form is [tex]4\sqrt{2-\sqrt{3} } (cos45^0+isin45^0)[/tex]

Part III: The expression of z² value in polar form is [tex]z^2 = 8(cos\frac{\pi}{8 }+isin \frac{\pi}{8} )\\[/tex]

Part IV:  The expression of w^4 in polar form is expressed as [tex]16(cos52.5^0+isin52.5^0)[/tex]

Complex numbers are the square roots of any negative numbers. They have both real and imaginary axis.

The rectangular form of expressing complex numbers is expressed as:

  • z = x + iy

The polar representation is expressed as:

  • r(cosθ - isinθ)

Given the complex numbers

z=√3-i

w=-2-2i

Part I: To express in polar form, we need to first get the modulus and argument of each of the complex numbers.

z= √3-i

|z| = [tex]\sqrt{(\sqrt{3} )^2+(-1)^2} \\[/tex]

[tex]|z| = \sqrt{3+1} \\|z|=\sqrt{4}\\|z|=2[/tex]

For the argument:

[tex]\theta = tan^{-1}\frac{y}{x}\\ \theta = tan^{-1}\frac{-1}{\sqrt{3} }\\\theta =-30^0\\[/tex]

Since tan is negative in the 3rd quadrant

[tex]\theta = 180 + 30\\\theta = 210^0[/tex]

The complex number √3-i in the polar form will be [tex]2(cos210^0+isin210^0)[/tex]

For the complex number:

z= -2-2i

|z| = [tex]\sqrt{(-2 )^2+(-2)^2} \\[/tex]

[tex]|z| = \sqrt{4+4} \\|z|=\sqrt{8}\\|z|=2\sqrt{2}[/tex]

For the argument:

[tex]\theta = tan^{-1}\frac{y}{x}\\ \theta = tan^{-1}\frac{-2}{\sqrt{-2} }\\\theta=tan^{-1}1\\\theta =45^0\\[/tex]

The complex number -2-2i in the polar form will be [tex]2\sqrt{2}(cos45^0+isin45^0)[/tex]

Part II: Taking the product of wz

(√3 - 1)(-2-2i)

Expand

wz = -2√3-2√3 i + 2 + 2i

wz = (-2√3+2) +(-2√3+2)i

Get the modulus

[tex]=\sqrt{(-2\sqrt{3}+2)^2+(-2\sqrt{3}+2)^2} \\=\sqrt{12-8\sqrt{3}+4 + 12-8\sqrt{3}+4 } \\=\sqrt{24-16\sqrt{3}+8}\\=\sqrt{32-16\sqrt{3} }\\=\sqrt{16(2-\sqrt{3} )}\\=4\sqrt{2-\sqrt{3} }[/tex]

Get the argument:

[tex]\theta = tan^{-1}\frac{-2\sqrt{3}+2}{-2\sqrt{3}+2}\\ \theta = tan^{-1}1\\\theta =45^0[/tex]

Expression in polar form is [tex]4\sqrt{2-\sqrt{3} } (cos45^0+isin45^0)[/tex]

Part III: To calculate z², we will simply square the polar form of z and apply De Moivre's theorem as shown:

Since z = [tex]2\sqrt{2}(cos45^0+isin45^0)[/tex]

[tex]z^2 = [2\sqrt{2}(cos\frac{\pi}{4}+isin\frac{\pi}{4} )]^2\\z^2 = (2\sqrt{2})^2(cos\frac{1}{2} * \frac{\pi}{4 }+isin\frac{1}{2} * \frac{\pi}{4} )]\\z^2 = 8(cos\frac{\pi}{8 }+isin \frac{\pi}{8} )\\[/tex]

This shows that the expression of z² value in polar form is [tex]z^2 = 8(cos\frac{\pi}{8 }+isin \frac{\pi}{8} )\\[/tex]

Part 4: We will also use De Moivre's theorem to get w⁴

Since w= [tex]2(cos210^0+isin210^0)[/tex]

[tex]w^4 = [2(cos210+isin210)]^4\\w^4 = 2^4(cos\frac{210}{4} +isin\frac{210}{4} )\\w^4=16(cos52.5^0+isin52.5^0)[/tex]

Hence the expression of w^4 in polar form is expressed as [tex]16(cos52.5^0+isin52.5^0)[/tex]

Learn more about complex numbers here: https://brainly.com/question/12375854